Foam superstabilization by polymer microrods - Alargova, Rossitza G (Langmuir : the ACS journal of surfaces and colloids, 2004)
Few foam systems stabilized by solid particles have been reported, and usually the particles have been used in combination with surfactants. We report how foams can be stabilized solely with a new class of anisotropic particles, hydrophobic polymer microrods of diameter less than 1 mum and length of a few tens of micrometers. The obtained foams were extraordinary stable, retaining a constant volume over many days and even surviving drying of most of the free liquid. The bubbles in these foams were sterically stabilized by dense thick "hairy" layers. The rigid intertwined protective shells around the bubbles did not allow the formation of thin films between them. The lifetime of these foams was orders of magnitude longer than the ones stabilized with typical foaming surfactants such as sodium dodecyl sulfate. The addition of sodium dodecyl sulfate led to hydrophilization of the microrods and suppressed the superstabilization effect. Thus, common foaming agents effectively act as defoamers for the ultrastable foams stabilized by microrods